Soil and climate characteristics and socio-economic data in the diagnostic of agroecosystems of São Carlos region, SP, Brazil - Pinto, Luís Fernando Guedes; Crestana, Silvio (Pesquisa Agropecuaria Brasileira, 2001)
Regional planning of agroecosystems is a key component in the sustainability of agriculture and it should consider the biophysical and socio-economic reality. Agriculture plays an important role in the region of São Carlos, SP, Brazil, but it is located in an area of environmental conservation. This work aimed to delimit the Agroecological Zone of this region and to diagnose agroecosystems through soil, climate and socio-economic data. The delimitation was based on climate, geomorphology and administrative division of the counties. The soils, land use, distribution of land ownership and the management were studied. The Zone delimited occupies 286,824.08 ha, and is composed by the Analândia, Itirapina, Santa Maria da Serra, São Carlos, São Pedro and Torrinha counties. There is potential for agriculture, existing mainly sandy and low fertility soils. Pastures and sugar cane are the main land use, the distribution of the ownership is unequal and there is risk of environmental degradation because the farmers do not use practices compatible with the natural features. It is recommended to adopt practices that emphasize soil conservation and correction and nutrient uptake. Species adapted to sandy soils with low demand for nutrients and resistant to water stress should be cultivated.